2021
DOI: 10.3758/s13423-021-01909-w
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence test items varying in capacity demands cannot be used to test the causality of working memory capacity for fluid intelligence

Abstract: There is a strong relationship between fluid intelligence and working memory capacity (WMC). Yet, the cognitive mechanisms underlying this relationship remain elusive. The capacity hypothesis states that this relationship is due to limitations in the amount of information that can be stored and held active in working memory. Previous research aimed at testing the capacity hypothesis assumed that it implies stronger relationships of intelligence test performance with WMC for test items with higher capacity dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, some other research has challenged the view that these capacity limits per se underlie the relation (e.g., Hagemann et al, 2023). Specifically, some studies showed that questions on fluid intelligence tests that are more cognitively demanding, and thus should require more working memory storage to be solved, do not correlate more strongly with working memory capacity (Salthouse & Pink, 2008;Burgoyne et al, 2019;Wiley et al, 2011;Unsworth & Engle, 2005; but also see Frischkorn & Oberauer, 2021;Smolen & Chuderski, 2015). Instead, it has been suggested that other aspects of working memory tasks such as attentional control processes (Draheim et al, 2022), the usage of encoding strategies (Babic et al, 2019), or the ability to adapt and apply rules (Salthouse & Pink, 2008;Wiley et al, 2011;Duncan et al, 2012) might be the crucial factors that drive the correlation between working memory performance and fluid intelligence.…”
Section: Visual Working Memory Performance Is Correlated With Fluid I...mentioning
confidence: 99%
“…However, some other research has challenged the view that these capacity limits per se underlie the relation (e.g., Hagemann et al, 2023). Specifically, some studies showed that questions on fluid intelligence tests that are more cognitively demanding, and thus should require more working memory storage to be solved, do not correlate more strongly with working memory capacity (Salthouse & Pink, 2008;Burgoyne et al, 2019;Wiley et al, 2011;Unsworth & Engle, 2005; but also see Frischkorn & Oberauer, 2021;Smolen & Chuderski, 2015). Instead, it has been suggested that other aspects of working memory tasks such as attentional control processes (Draheim et al, 2022), the usage of encoding strategies (Babic et al, 2019), or the ability to adapt and apply rules (Salthouse & Pink, 2008;Wiley et al, 2011;Duncan et al, 2012) might be the crucial factors that drive the correlation between working memory performance and fluid intelligence.…”
Section: Visual Working Memory Performance Is Correlated With Fluid I...mentioning
confidence: 99%
“…Kovacs and Conway (2016), in the context of their process overlap theory, conclude that the link between WM and Gf is driven by the operation of multiple domain-general cognitive processes which are involved in both groups of task, measuring Gf and WM. Despite years of research and numerous results confirming the relationship between WM and Gf, researchers have been unable to provide a conclusive answer as to why the two constructs are related, and the question of what explains this relationship remains open (Burgoyne et al, 2019;Frischkorn & Oberauer, 2021;Harrison et al, 2015).…”
Section: Relationship Between Working Memory and Fluid Intelligencementioning
confidence: 99%